PHILIPPINE K TO 12 CURRICULUM AND PROGRAMME FOR INTERNATIONAL STUDENT ASSESSMENT (PISA) 2018 READING LITERACY PARALLELISM AND TEACHING-LEARNING EXPERIENCES - Galang, Aljon (ETERNAL (English, Teaching, Learning, and Research Journal), 2020)
Philippine K-12 Curriculum and Programme for International Student Assessment 2018 Reading Literacy Parallelism and Teaching-Learning Experiences.. Objectives: This study is made to capture the instructional system and learning milieu of the PISA 2018 Reading Literacy-Related Senior High School Subjects aiming to evaluate its curriculum design and implementation.Methods: The study used Illuminative Evaluation Model to evaluate the curriculum design and implementation by gauging the instructional system through heat mapping and the learning milieu of teacher participants and graduate respondents through survey, interview, and researcher’s past observation. Findings: In the study, it was found out that: (a) the K to 12 program through the learning competencies is 28.64% parallel with the PISA 2018 Reading Literacy Skill Framework; (b) teachers implement the curriculum in which the Reading Literacy Skills are reflected even under various teaching-learning constraints.; (c) the graduate respondents (GRs) are good in terms of locating information but need improvement in evaluating and reflecting on and/or among texts specifically the skill ‘detecting and handling conflict’. Moreover, GRs associate learning the PISA 2018 Reading Literacy Skills the most from the subjects Reading and Writing Skills and Practical Research and the least from 21st Century Literature.Conclusion: The K-12 program through learning competencies is 28.64% parallel with PISA 2018 Reading Literacy Skill Framework. This shows one of the characteristics of the written curriculum or the instructional system.